PESAN-PESAN MORAL DALAM CERITA PENDEK YOUNG GOODMAN BROWN DAN RAPPACCINIâ€™S DAUGHTER KARYA NATHANIEL HAWTHORNE - KUMOWAL, JOAN FRATY (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2013)
The skripsi which is entitled â€œPesan-Pesan Moral dalam Cerita Pendek Young Goodman Brown dan Rappacciniâ€™s Daughter Karya Nathaniel Hawthorne,â€ aims at identifying, analyzing and describing the moral messages through the character, setting and plot. The data had been collected by focusing on the character, setting and plot as the elements of prose which reveal the moral messages within Young Goodman Brown and Rappacciniâ€™s Daughter. In identifying the character, the writer uses theory of Roberts concerning character as the representation of human being. The writer also uses theory of Stanton to identify setting as the place or situation of the story and plot as the whole sequence of the story. In order to analyze the moral messages within Young Goodman Brown and Rappacciniâ€™s Daughter, the writer uses theory of Sidney about the purposes of literature which are to educate and entertain the readers. The findings of this research show that literary works have the moral messages which are portrayed by the intrinsic elements of the short stories and those show the didactic and entertaining functions of literature. The moral messages in Young Goodman Brown are: the housewifeâ€™s power of love in marriage, choice of life determines the future and human should have the consistency in making a decission. Rappacciniâ€™s Daughter also has three moral messages, those are: the children are not their parents medium of exploitation, physical appearance does not always reflect humanâ€™s behaviour and sincerity of love makes everything good. Both short stories have two similarities of the moral messages, those are love and choice of life. Keywords: â€œYoung Goodman Brownâ€, â€œRappacciniâ€™s Daughterâ€, Moral Messages, Short Story